Extramedullary Hematopoiesis Presenting as Bilateral Glomus Tympanicum—First Case Report in a Pediatric Patient and With Bilateral Presentation. (May 2018) - Chen, Leonard N; Espinel, Alexandra; Reilly, Brian; Luca, Dragos C
To the best of our knowledge, this is the first case report of middle ear extramedullary hematopoiesis (EMH) in a pediatric patient as well as the first bilateral presentation reported in both children and adults. We report a 13-year-old African-American female with sickle cell disease who developed bilateral hearing loss, with magnetic resonance imaging findings consistent with bilateral glomus tympanicum (GT). Upon excisional biopsy, however, EMH was diagnosed histologically. Besides its novelty, this case highlights the importance of considering EMH in the differential diagnosis of GT including cases with bilateral presentation that may be otherwise highly suggestive of the familial form of GT.